The absolute competence of the industrial relations court in resolving employment termination disputes - Ndun, Ivan (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: The jurisdictional scope or competence of the Industrial Relations Court is elaborated in Section 56, Law Number 2, of 2004. However, Section 56 Number Law 2 Years 2004 has spurred further debate regarding the proper competence of the Industrial Relations Court because, under this law, the Court has issued ineffective and inefficient decisions. In response to this debate, this study problematizes the competence of the Industrial Relations Court in presiding over the termination of employment contracts in Indonesia. Method: In analyzing the problem, this research uses a normative juridical method that has a systematic way of conducting research, focusing on competency theory, the theory of justice and supremacy of law, subjective justice, competency of the Industrial Relations Court according to existing laws and regulations, and experts’ views regarding the contribution of the existing literature to the competency of Industrial Relations Court judges. Results: This study argues that an excess of laws governs the termination of employment contracts, which supposedly lies under the competence of the Industrial Relations Court. Hence, to protect the rights of employees in the context of industrial relations, a judicial review of Law Number 2 Year 2004 on Manpower is required. Conclusions: The Industrial Relations Court’s jurisdiction is overly broad, requiring a legislative review to ensure clarity, justice, and legal certainty. Limitations: This research has several limitations, including the time required to search for additional references, such as the latest journals, and comparisons with the competence of industrial relations courts in various countries. Contributions: It is hoped that the results of this research can provide information as a basis for consideration and contribution of thought to policymakers in formulating laws and regulations more effectively and efficiently to bring justice, legal certainty, and benefits to society.